Hippocampal involvement in nonpathological déjà vu: Subfield vulnerability rather than temporal lobe epilepsy equivalent. Issue 7 (5th June 2018) - Pešlová, Eva; Mareček, Radek; Shaw, Daniel J.; Kašpárek, Tomáš; Pail, Martin; Brázdil, Milan
Abstract: Introduction: Morphological correlates of nonpathological déjà vu (DV) have been identified recently within the human brain. Significantly reduced gray matter volume (GMV) within a set of cortical and subcortical regions reported in subjects experiencing DV seems to mirror the distribution of GMV reduction in mesial temporal lobe epilepsy (MTLE) patients but vary in terms of the hippocampus. Another condition associated with hippocampal GMV reduction and DV alike disturbance in memory processing is schizophrenia (SCH). Here, we tested the hypothesis that hippocampal involvement in nonpathological DV resembles more closely the pattern of GMV decrease observed in MTLE compared with that occurring in SCH. Methods: Using automated segmentation of the MRI data we compared the medians of GMV within 12 specific hippocampal subfields in healthy individuals that do (DV+; N = 87) and do not report déjà vu experience (DV−; N = 26), and patients with MTLE ( N = 47) and SCH ( N = 29). By Pearson correlation, we then evaluated the similarity of MTLE and SCH groups to DV+ group with respect to spatial distribution of GMV deviation from DV− group. Results: Significant GMV decrease was found in MTLE group in most of the subfields. There were just trends in the hippocampal GMV decrease found in DV+ or SCH groups. Concerning the spatial distribution of GMV decrease, we revealed statistically significant correlation for the left hippocampus for SCH vs DV+. Otherwise there was no statistically significant correlation. Conclusions: Our findings reveal structural features of hippocampal involvement in nonpathological DV, MTLE, and SCH. Despite our expectations, the pattern of GMV reduction in the DV+ relative to the DV− group does not resemble the pattern observed in MTLE any more than that observed in SCH. The highly similar patterns of the three clinical groups rather suggest an increased vulnerability of certain hippocampal subfields; namely, Cornu Ammonis (CA)4, CA3, dentate gyrus granular cell layer (GC‐DG), hippocampal–amygdaloid transition area (HATA) and subiculum. Abstract : This study reveals structural features of hippocampal involvement in non‐pathological déjà vu (DV), mesial temporal lobe epilepsy (MTLE) and schizophrenia (SCH) using automated segmentation of the MRI data. In contrast to the examined hypothesis, the better correlation between DV and SCH was found, which supposedly reflects increased vulnerability of distinctive hippocampal subfields to adverse conditions.